The emergence of e-learning and online-based training during the COVID-19 crisis: an exploratory investigation from Bangladesh - Shamsul Huq Bin Shahriar; Sayed Arafat; Intijamul Islam; J. M. Ekram Hossain Nur; Saifur Rahman; Syful Islam Khan; M. Sayeed Alam (Management Matters, 2023)
Purpose – The extreme measures that have been taken by governments across the globe to minimize the spread of COVID-19 have had significant impacts on almost all the public sectors, especially on the economy and education. This study aims to address the approaches and prospective of online-based training and e-learning for employee learning and development during this COVID-19 crisis. Design/methodology/approach – With an emphasis on the qualitative approach and considering the complex COVID-19 emergency, required data were collected from in-depth interviews to interpret the experiences of the respondents. Findings – The findings suggested that the digital learning ecosystem offered flexibility of time, place and pace, which provided essential convenience during the COVID-19 crisis. From the human resource (HR) perspective, the e-learning culture has enabled the organizations to quickly adopt the new normal, secure sustainable continuity of organizational development and ensure decent work and growth within and across organizations. The adoption of e-learning and flexible working conditions following the setback has enabled the organizations to quickly cope up with the new normal, causing a significant paradigm shift in the organizational culture and corporate sector of Bangladesh. Research limitations/implications – The study will assist the HR of any organization to contemplate e-learning systems as effective alternative training methods. Also, the study will be suggestive to traverse new dimensions and skillsets for the pedagogues. Originality/value – This study offers new evidential scenarios regarding the emergence of effective e-learning initiatives and online-based learning programs for developing the workforce to be efficient and productive even in distressful and inconvenient COVID-19 situations.